(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
The isolated cultures of medicinal plants of Armenian flora Ajuga genevensis L. and Ajuga chia Schreb. were obtained. The growth indices and cytomorphological characteristics were shown.